Selected aspects of measuring coopetition in the context of entrepreneurial orientation - Kusa, Rafał (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
In searching and exploring entrepreneurial opportunities, entrepreneurs can both compete and cooperate, also with their competitors. The aim of the paper is to identify possible associations between organisational entrepreneurship and coopetition. In the paper, the coopetition intensity coefficient is proposed. The results of the study show that this coefficient is significantly correlated with dimensions of entrepreneurial orientation (risk-taking and innovativeness) and performance of a firm. Additionally, some research items are proposed, that can be utilized for deeper diagnosis of coopetitive behaviours related to attributes of entrepreneurship (dimensions of entrepreneurial orientation) as well as stages of entrepreneurial process (opportunity identification, entrepreneurial planning, initiating and managing the resulting enterprise).